Hair removal using a long-pulsed Nd:YAG Laser: Comparison at fluences of 50, 80, and 100 J/cm2 - David J. Goldberg (2018)
BACKGROUND. Unwanted hair is a widespread cosmetic problem. Many temporary methods of hair removal have proved unsatisfactory. A variety of laser systems with varying wave-lengths, pulse durations, and energy fluences are currently utilized for hair removal. Optimal laser parameters continue to require further investigation. OBJECTIVE. To evaluate the efficacy and safety of a long-pulse millisecond Nd:YAG hair removal laser utilizing fluences of either 50, 80, or 100 J/cm2. METHODS. Fifteen subjects were treated with a contact cooled 50 msec Nd:YAG laser at fluences 30, 50, or 100 J/cm2. Reduction in hair regrowth was measured at 3 months after treatment by comparing the terminal hair count to the baseline values. Potential complications were also evaluated. RESULTS. Average hair reduction at 3 months after treatment was 29%, 29%, and 27% in areas treated with a 50-msec Nd:YAG laser at fluences of 50, 80, and 100 J/cm2, respectively. Although short-term blistering was noted in two subjects, no hyperpimentation, hypopigmentation, or scarring was observed at 3 months after treatment. CONCLUSION. Long-pulse millisecond Nd:YAG laser hair removal with fluences of either 50, 80, or 100 J/cm2leads to similar efficacy with no significant adverse effects.